The Politics of Non‐Existence - Setälä, Maija (2024)
This article argues that the representation of future generations is likely to remain inadequate because of the lack of accountability mechanisms characteristic of representative relations among contemporaries. Two problems pertaining to the representation of future generations and their interests are distinguished, namely misrepresentation and negligence. Misrepresentation refers to ill-informed, biased, and purposive interpretations regarding the interests of future generations, whereas negligence involves future interests not being properly considered in policymaking. While these two problems are often intertwined, misrepresentation is a problem of epistemic and normative judgments, whereas negligence is a motivational problem. The interests of future generations are especially likely to be neglected in cases of so-called intergenerational conflict, that is, situations of welfare tradeoffs between present and future generations. Inclusive democratic deliberation is a remedy for misrepresentation, but its capacity to address negligence may be more limited. Finally, the article remarks on the role of future-regarding deliberation in representative democratic systems.